2023
DOI: 10.1164/rccm.202303-0505oc
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease Self-Management in Three Low- and Middle-Income Countries: A Pilot Randomized Trial

Suzanne L. Pollard,
Trishul Siddharthan,
Shakir Hossen
et al.

Abstract: Objectives Chronic obstructive pulmonary disease (COPD) disproportionately affects low- and middle-income countries. Health systems are ill prepared to manage the increase in COPD cases. Methods We performed a pilot effectiveness-implementation randomized field trial of a community health worker (CHW)-supported, 1-year self-management intervention in individuals with COPD grades B–D. The study took place in low-resource settings of Nepal, Peru, and Uganda. The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In this issue of the Journal , Pollard and colleagues (pp. 1052–1062 ) have addressed this question through a pilot study conducted in resource-limited settings from three different continents ( 7 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of the Journal , Pollard and colleagues (pp. 1052–1062 ) have addressed this question through a pilot study conducted in resource-limited settings from three different continents ( 7 ).…”
mentioning
confidence: 99%
“…GECo (Global Excellence in COPD Outcomes) is a multinational study that was aimed at investigating the diagnostic accuracy of case finding for COPD using a questionnaire with or without peak flow meter versus gold standard spirometry (GECo-1) ( 8 ) and the effectiveness of a multifaceted intervention comprising a self-directed COPD action plan delivered and supported by CHWs for the management of COPD exacerbations (GECo-2) ( 7 ). The study was conducted in Peru, Uganda, and Nepal and reported a COPD prevalence of 2.7%, 7.4%, and 18.2%, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation